Model of a Switched Reluctance Generator Considering Iron Losses, Mutual Coupling and Remanent Magnetism - Šime Grbin; Dinko Vukadinović; Mateo Bašić (Energies)
In this paper, an advanced model of a switched reluctance generator (SRG) with mutual coupling, iron losses, and remanent magnetism is presented. The proposed equivalent circuit for each SRG phase is represented by the winding resistance, phase inductance and electromotive forces (EMFs) induced by mutual flux-linkage and remanent magnetism. In the advanced SRG model, the phase inductance and equivalent iron-loss resistance need not be known, as the components of the phase current flowing through them are determined directly from appropriate look-up tables, making the advanced SRG model simpler. Both the magnitude of the mutual flux-linkage and its time derivative are considered in the advanced model. The proposed model only requires knowledge of data that can be obtained using the DC excitation method and does not require knowledge of the SRG material properties. For the first time, the remanent magnetic flux of the SRG is modeled and the induced EMS caused by it is included in the advanced SRG model. Stray losses within the SRG are considered negligible. Connection to an asymmetric bridge converter is assumed. Magnetization angles of individual SRG phases are provided by the terminal voltage controller. The results obtained with the advanced SRG model are compared with experiments carried out in the steady-state of the 8/6 SRG with a rated power of 1.1 kW SRG over a wide range of load, terminal voltage, turn-on angle, and rotor speed in single-pulse mode suitable for high-speed applications.